Skin Color and Academic Achievement in Young, Latino Children: Impacts across Gender and Ethnic Group - Kim, Yeonwoo (Cultur Divers Ethnic Minor Psychol, 2018)
OBJECTIVES: The present study investigates the association between skin color and academic achievement in young Latino students. METHODS: Data were drawn from a longitudinal study of the early development of Latino children that took place in 24 public elementary schools in New York City. Students included in the present analyses (N=750) were 4- and 5-years old when they were enrolled (baseline) and were followed through the end of first grade. Structural equation models and bootstrapping mediation tests were conducted to examine the effects of skin color on academic achievement at the end of first grade, partially mediated by academic and social emotional domains of school readiness in pre-kindergarten or kindergarten. This study considered the intersectionality of ethnicity and gender in the models. RESULTS: The findings showed that for Dominican-origin boys, being “collectively black” was indirectly associated with lower academic achievement in first grade, mediated by lower teacher-rated adaptive behavior in pre-kindergarten or kindergarten. CONCLUSIONS: Discussion focuses on the need for educational policies and practices to be conscious of phenotypicality bias.